Reforma ochrony danych osobowych ‒ konsekwencje ograniczonego stosowania ogólnego rozporządzenia o ochronie danych w sferze publiczno-prawnej (zagadnienia wybrane) - Jabłoński, Mariusz; Wygoda, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The main purpose of this elaboration is to present the analyses of rules, the procedure (mode) of realization the right of protection personal data. Authors focuses on presenting the meaning of notions: the General Data Protection Regulation (GDPR), Directive 95/46/EC (General Data Protection Regulation) and Directive (EU) 2016/680 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data by competent authorities for the purposes of the prevention, investigation, detection or prosecution of criminal offences or the execution of criminal penalties, and on the free movement of such data, and repealing Council Framework Decision 2008/977/JHA; data protection, the data controller, dataset custodian with particular reference to the performance of this function by the authorities and other public bodies. The specifics of their activities in the area of personal data was presented on the example of the probation officer. As of 25 May 2018, the General Data Protection Regulation (GDPR) will apply to the processing of personal data in the context of the activities of an establishment of a controller or processor. At the same time wide ranging autonomy granted as regards technical, organizational and documenting standards to be applied in processes of personal data processing enforces profound changes in one of the fundamental principles of public authorities and bodies activity. Unification of high administration fines across the entire EU for infringements of Regulation will probably impose significant modifications in so far usedpractices of personal data processing. Additional trigger points for changes will be also amendments to the domestic acts at both general and sectoral level being under legislation now. Particularly deep changes will concern the legal basis of the police, prosecution, courts and even probation officers.
Keywords: commemorative book; constitutionalism; Constitution; democracy; human rights; right to court; freedoms and rights